Enhancing the value of comparative exposure assessment in alternatives assessment - Meng, Qingyu; Zhou, Xiaoying (Frontiers in Sustainability, 2023)
Reducing chemical exposure is a crucial principle in alternative assessment (AA) frameworks. Since the release of the report, A Framework to Guide Selection of Chemical Alternatives by the National Research Council in 2014, comparative exposure assessment (CEA) has been increasingly viewed as an essential part of selecting safer alternatives to chemicals of concern in consumer products. However, CEA has not been fully integrated into existing AA frameworks. CEA remains merely a technical step, disconnected from other AA components. This paper advocates for the integration of CEA as an essential part of AA, providing a holistic approach to identifying safer alternatives. The paper aims to illustrate the connection between CEA and other AA components, such as problem formulation, hazard assessment, life cycle assessment, economic assessment, and decision-making. It suggests systematic integration of CEA with cross-cutting AA considerations, including transparency, uncertainty, chemical mixtures, and sensitive receptors. This integration will enable the selection of a fit-for-purpose CEA approach based on the decision context and foster a more comprehensive approach to identifying safer alternatives. While the examples provided are not exhaustive, they aim to encourage further discussion on the integration of CEA into AA.